The Evaluation of Breast Milk Perception: Midwifery and Nursing Students - BULUT, Aliye; BAYRAKÇI, Elif (Göbeklitepe Medical Science Journal, 2021)
Objective: The present study was carried out with the aim of determining the perceptions of the students studying in the Department of Midwifery and Nursing about breast milk. Method: The population of the research consisted of midwifery and nursing students studying at Gaziantep Islam, Science and Technology University, Faculty of Health Sciences. The research data was collected using a questionnaire containing the socio-demographic data of the students and the "Breast Milk Perception Scale for Adults". Results: When the distribution by departments was examined, it was found that the rate of midwifery students was 32.6%, and the rate of nursing department students was 67.4%. The level of breast milk perception of midwifery department students was significantly higher than that of nursing department students. When the change in the level of perception of breast milk according to the education level of the father was examined, it was observed that there was a significant difference (p<0.05). The perception of breast milk of participants whose fathers have a master’s degree was significantly lower than those whose fathers have other educational levels. When the change in the level of perception of breast milk according to the father’s occupation was examined, it was observed that there was a significant difference (p<0.05).Conclusion: A significant difference was found between the students studying in the midwifery and nursing departments according to the scale total score averages, and the scale score average was found to be higher for the midwifery department students than the nursing department students. It was determined that gender, age, place of residency, and socio-economic status did not change the perception of breast milk. Nurses and midwives play a key role in this regard and should pay due attention to breastfeeding, which has the most important place in creating a healthy society.